IMPROVEMENT OF GRAIN TRANSPORTATION TECHNOLOGY FROM COMBINES - FRYSHEV, Sergii; LUKACH, Vasyl; IKALCHYK, Mykola; VASYLYUK, Volodymyr (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article provides a rationale for an improved technological process for transporting grain from grain combines (ЗK) by a semi-trailer dump truck (НП) in an aggregate with a tractor and a saddle trailer. One of the main reserves for increasing the productivity of a combine is to increase the utilization factor of its shift time by using transshipment technology based on interoperation compensators - tractor trailers for reloaders of the PBN-30, PBN-40, PBN-50 brands, etc. and heavy vehicles (AT), in the body which grain is being reloaded outside the field. The lack of technology is significant downtime of vehicles. A comparative analysis of various technological schemes for the operation of the (ЗK) and vehicles showed that the minimum specific duration of harvesting and transport operations is achieved by using a tractor with a tractor to work in the field, subject to the minimum time spent on the formation (uncoupling, hitching) of transport units using a fifth wheel coupling device, which fitted with a trailer. At the same time, vehicles are used as negotiable (НП)s, which makes it possible to organize the continuous operation of tractors in the sections “ЗК - edge of the field” and “edge of the field - grain receiving point”, where possible downtime of the AT is replaced by downtime only of the НП. We have proposed a technical solution containing a temporary redistribution of the mass of grain in the body of the НП by loading it into the front part of the body. At the same time, the rear wheels of the НП are partially unloaded and do not over-compact the soil, and the rolling semi-trailer, equipped with wide-profile low-pressure tires, perceives additional load without significant soil compaction. The theoretical analysis of the rhythm of the processes of grain movement by individual technological links of the harvesting and transport complex made it possible to determine the analytical dependences of the main parameters of these links on the productivity of the grain combine and the volume of its bunker, the nominal load capacity of the НП, the duration of the НП recoupling, the distance of grain transportation, the average technical speed of the tractor and the car. The use of semi-shuttle transporters operating in two stages: in the field and on the road, provides a 1.5-fold increase in the productivity (average output) of the AT, and also eliminates the cost of specialized reloading trailers and double reloading of grain.